Content analysis of conversations on Reddit: reactions to FDA’s ENDS prioritized enforcement policy - Guillory, Jamie; Trigger, Sarah; Brophy, Jenna; Ross, Ashley; Lane, Stephanie; Kim, Annice; Nonnemaker, James; Liu, Sherry T.; Snyder, Kimberly; Delahanty, Janine (Frontiers in Communication, 2024)
Introduction: On January 2, 2020, the FDA announced a policy focused in part on prioritizing enforcement of flavored (other than tobacco-or menthol-flavored) cartridge-based electronic nicotine delivery systems (ENDS) without premarket authorization. Methods: We used a query to identify Reddit conversations relevant to the policy from January 2 to May 6, 2020. Our sample included 576 posts (46 posts and 530 accompanying comments). Two analysts coded posts for mentions of use behaviors (e.g., switching, quitting), purchasing behaviors (e.g., purchasing from retailer new to the user), and flavored products. We summarized frequencies of coded data and provided illustrative quotes. Results: Only 21.0% (121/576) of posts mentioned use behavior. Switching behavior was the most common use behavior mentioned (50.4%, 61/121). Most switching behavior posts focused on ENDSrelated switching (91.8%, 56/61). The most common ENDS-related switching behaviors mentioned were switching to an open tank (45.9%, 28/61) or device with refillable pods/cartridges (44.3%, 27/61); 8.2% (5/61) mentioned switching to disposables. Just 15.5% (89/576) of posts mentioned purchasing behavior, with the most common being purchasing from a retailer new to the user (32.6%, 29/89). Only 6.8% (39/576) of posts mentioned specific flavors. Conclusions: Reddit posts about the policy commonly discussed switching to non-cartridge-based ENDS products, such as open tank systems or disposable devices, and purchasing products from different online sources that were still selling these products. Findings suggest that publicly available Reddit data can complement data from traditional sources (e.g., surveys, sales) to understand potential unintended consequences associated with policies by exploring the public's reactions.